Yeast as a model system to study RecQ helicase function - Ashton, Thomas M.; Hickson, Ian D. (DNA repair, 2010)
Mutations in the highly conserved RecQ helicase, BLM, cause the rare cancer predisposition disorder, Bloom's syndrome. The orthologues of BLM in Saccharomyces cerevisiae and Schizosaccharomyces pombe are SGS1 and rqh1+, respectively. Studies in these yeast species have revealed a plethora of roles for the Sgs1 and Rqh1 proteins in repair of double strand breaks, restart of stalled replication forks, processing of aberrant intermediates that arise during meiotic recombination, and maintenance of telomeres. In this review, we focus on the known roles of Sgs1 and Rqh1 and how studies in yeast species have improved our knowledge of how BLM suppresses neoplastic transformation.